2005
DOI: 10.1191/0959683605hl861ra
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotope evidence for an abrupt reduction in grasses coincident with European settlement of Lake Eyre, South Australia

Abstract: Stable carbon isotopes in emu eggshell (EES) reflect emu diets and consequently the vegetation available for food sources. At Lake Eyre, South Australia, isotopic data suggest that there has been a rapid and dramatic change in vegetation at some point over the last 200 years when compared with the rest of the Holocene. The proportion of C4 plants in emu diets has been reduced by approximately 20% in response to an overall shift in C4/C3 biomass at Lake Eyre. Isotopic measurement of the dominant plants at Lake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Hence, C4 plants do not contribute substantially to Dromaius' diet even though they dominate the landscape. Analyses of modern (1970-2000 AD) Dromaius eggshells from the Lake Eyre region show virtually no C4 elements in the birds' diets even though canegrass (C4) is a dominant vegetation type (Johnson et al, 2005).…”
Section: Paleodietary Reconstructionsmentioning
confidence: 99%
“…Hence, C4 plants do not contribute substantially to Dromaius' diet even though they dominate the landscape. Analyses of modern (1970-2000 AD) Dromaius eggshells from the Lake Eyre region show virtually no C4 elements in the birds' diets even though canegrass (C4) is a dominant vegetation type (Johnson et al, 2005).…”
Section: Paleodietary Reconstructionsmentioning
confidence: 99%
“…The rainfall-dependent grasslands and arid regions of the LEB also contain rare and endangered species of plants and animals (Morton et al, 1995), in addition to supporting a large cattle (and to a lesser extent, sheep) grazing industry. The terrestrial ecosystems have shown evidence of degradation since European settlement, with changes in vegetation (Johnson et al, 2005) and significant mammalian extinctions (McKenzie et al, 2007). Management of natural ecosystems and human activities requires a well-founded knowledge of rainfall and streamflow patterns within the LEB.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive areas of stony ("gibber") and bare surfaces mantle the slopes and plains. Changes in vegetation cover (Johnson et al, 2005) and geomorphic processes occurred with the shift from Indigenous hunter-gathering to Europeanstyle pastoralism in the 19th century (Fanning, 1994(Fanning, , 1999Noble & Tongway, 1986;Pickard, 1994). Topsoil lost from the hillslopes was deposited on valley floors as laminated and cross-bedded sandy sediments [variously termed post-settlement alluvium (PSA) or post-European material (PEM); Gore et al, 2000:117].…”
Section: The Geomorphic Contextmentioning
confidence: 99%